Embedding Disability in the Social Work Curriculum - Blundell, Barbara; Fernandes, Christina; Ridley, Sophie; Warren, Amy; Stewart, Cath; Watts, Lynelle (2022)
There have long been calls for disability to have an increased profile in social work education; however, the launch of the National Disability Insurance Scheme in 2013 has rendered this call more urgent. Curtin University graduates and students participating in fieldwork are required to have knowledge of current policy implications on practice, develop skills in this area and uphold social work values in this field of practice. Social workers are employed both directly and indirectly in the disability sector, which is facing workforce issues pertaining to recruitment and retention. Academic staff teaching in both the Bachelor (BSW) and Master of Social Work Qualifying (MSWQ) courses at Curtin identified that the curricula on disability and the NDIS in both courses requires strengthening. Additionally, anecdotal feedback from current and past students and industry partners suggests that a more comprehensive review in this area is warranted. This research project focussed on identifying curricula gaps through an active partnership with industry, alumni and students, with the overall aim of developing topical, relevant, and contemporary content on disability and the NDIS in Australia. Current BSW and MSWQ students, recent graduates, and social work practitioners who work in the disability sector were surveyed about their perspectives on existing and required disability and NDIS content in the curriculum. The next phase of the project will involve participants in co-creating new curricula to address the identified gaps.